Rehabilitation planning for children and adolescents with cerebral palsy - Jeglinsky, Ira; Salminen, Anna-Liisa; Carlberg, Eva Brogren; Autti-Rämö, Ilona (Journal of pediatric rehabilitation medicine, 2012)
Objective: To explore the types of procedures and practices in rehabilitation planning for children with cerebral palsy and how multidisciplinary team members experience them. Design, subjects, and setting: A qualitative research approach was used. Participants were members of multidisciplinary teams in neuropediatric wards at five university hospitals. Methods: In order to explore the rehabilitation planning procedure within multidisciplinary teams, focus group interviews were conducted. The interviews were tape recorded and transcribed. Three content areas guided the interviews: goal setting, the different transition phases, and the use of the International Classification of Functioning, Disability and Health, Child and Youth version (ICF-CY). Qualitative content analysis was used to analyze the results. Results: Three themes arose from the focus group discussions; challenging goal setting, transition without routines, and ICF-CY not in use. A family-centered service model had been adopted, but there was no clear procedure in the collaboration with parents. Goal setting was found to be challenging and the concern arose of how to integrate goals into the child's everyday life. There was a lack of systematic planning of the different transition phases. There was also a general variation in the rehabilitation planning procedures due to local and regional differences in practice. The ICF-CY was familiar, but not in formal use in clinical practice. Conclusion: There is a need to enhance the procedures and to systematize coordination of services in the rehabilitation process. The ICF-CY framework might help to optimize collaborative goal setting and to structure both procedures and documentation of the rehabilitation plans and goals.